Faktor-Faktor yang Memengaruhi Realisasi Pembiayaan Mikro (Studi Kasus PT Bank Syariah Mandiri KCP Bogor Merdeka) - Samirah Ali; Ali Mutasowifin (Institut Pertanian Bogor, 2015)
Microfinance is one popular product of Bank Syariah Mandiri. The purpose of this study is to know factors that influence the realization of microfinance as well as the characteristics of microfinance debitors. Characteristics of microfinance debitors are dominated by male, age 31-40 years old, high school education, 2-4 people dependents family, over 2 years age of business, net income per month from Rp1,000,000 to Rp5,000,000, dominated by trading companies, 1-3 times of borrowing frequency, amount of financing is more than Rp20,000.000, value of collateral is more than Rp50,000,000, and purpose of financing is for productive activities. Using multiple linear regression analysis, F test and T test at α = 5% there are three variables affect the realization of microfinancing, namely type of business (trade), the amount of financing proposed and value of collateral.